Etika Al-Qur’an Terhadap Non-Muslim - Harda Armayanto (Universitas Darussalam Gontor, 2013)
This paper describes the ethics toward non-Muslims based on al-Qur’an. Islam as a religion of peace was accused and insulted by the orientalists frequently. These accusations and insulting stated in several articles, journals either in their books. Their books like Islamic Invasion wrote by Robert Morey and Islam Revealed by Anis A Shorrosh are some sample of how the orientalists discredits Islam. Whereas Islam is not like what they accused. On the contrary, Islam has responding their accusations with an elegant and tolerant doctrine. Islam has teaches its peoples to respects another religion’s people, Islam forbids his people to insult other religions, to excoriate their worships or forcing non-Muslims to convert or believes to Islam, even Islam teaches its people to acknowledge non-Muslims as brother and sister. This is Islam’s admiration toward non- Muslims. Surprisingly, these admirations inversely proportional to what non- Muslims did toward Islam and its people. The abuses as what we mention it before, was being happened even until now. Lately, one of Christian pastor in United State was told his people to burn the Holly Qur’an or as we known about suppression of Rohingya’s Muslims that was did by Myanmar’s Buddhists.